2004
DOI: 10.1074/jbc.m307006200
|View full text |Cite
|
Sign up to set email alerts
|

The Short Stature Homeodomain Protein SHOX Induces Cellular Growth Arrest and Apoptosis and Is Expressed in Human Growth Plate Chondrocytes

Abstract: Mutations in the homeobox gene SHOX cause growth retardation and the skeletal abnormalities associated with Lé ri-Weill, Langer, and Turner syndromes. Little is known about the mechanism underlying these SHOXrelated inherited disorders of bone formation. Here we demonstrate that SHOX expression in osteogenic stable cell lines, primary oral fibroblasts, and primary chondrocytes leads to cell cycle arrest and apoptosis. These events are associated with alterations in the expression of several cellular genes, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 39 publications
4
99
1
2
Order By: Relevance
“…In the human growth plate, SHOX is solely expressed in chondrocytes, as opposed to osteoblasts or osteoclasts, and plays a fundamental role in chondrocyte proliferation, hypertrophy, and apoptosis, a process that results in the formation of a cartilage framework serving as a template for osteogenesis. (43) Histopathological studies of growth plate morphology in patients with Lé ri-Weill dyschondrosteosis have showed a widespread disorganization of the normal parallel columnar arrangement of chondrocytes. (44) Speculatively, this disorganization may preferentially exert effects on the bone inside, thereby compromising trabecular architecture rather than on the perichondral bone formation that creates a collar of cortical bone.…”
Section: Discussionmentioning
confidence: 99%
“…In the human growth plate, SHOX is solely expressed in chondrocytes, as opposed to osteoblasts or osteoclasts, and plays a fundamental role in chondrocyte proliferation, hypertrophy, and apoptosis, a process that results in the formation of a cartilage framework serving as a template for osteogenesis. (43) Histopathological studies of growth plate morphology in patients with Lé ri-Weill dyschondrosteosis have showed a widespread disorganization of the normal parallel columnar arrangement of chondrocytes. (44) Speculatively, this disorganization may preferentially exert effects on the bone inside, thereby compromising trabecular architecture rather than on the perichondral bone formation that creates a collar of cortical bone.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we showed, through a precise analysis of AH with respect to target height, that patients with XrX, isoXq, and, to a lesser extent 45,X had more severe growth deficits in terms of both spontaneous growth and growth after GH treatment than those of other karyotype subgroups, highlighting the major role of X chromosome dosage in growth not only for spontaneous pre and postnatal growth but also after height improvement due to GH therapy. The effect of the SHOX gene on height is well documented, for both fetal and postnatal growth (15,16,17,18). However, little is known about the contribution of other genes to growth.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Its main effect is to promote differentiation and to stop the proliferation of hypertrophic growth plate chondrocytes. Haploinsufficiency results in the excessive proliferation of these chondrocytes and a premature fusion of the growth plate (17,18). SHOX gene function is dosage dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no evidence to support that SHOX is alternatively spliced during chondrogenesis, it presents as a good candidate. Although both Cbf␣1 and SHOX are expressed in differentiating chondrocytes (Akiyama et al, 1999;Marchini et al, 2004), Prx1 isoforms are expressed at an earlier time in the chondrogenic process, in the prechondrogenic mesenchyme and perichondrium. Thus, Prx1 is novel in the antagonistic function of its two isoforms present during the early stages of chondrogenesis.…”
Section: Discussionmentioning
confidence: 99%